Analysis of The Influence of Service Quality, Prices and Perceptions Taste Towards Customer Satisfaction and Loyalty at The Store “Mie Liho Mie Kiro” Gresik - Maimunah, Siti; Sardjono, Sigit (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2024)
Marketing is a business activity that consists of a process in planning consumer needs, creating a product that is suitable for marketing, promoting, and distributing products or services. One the efforts made the company in marketing is by being able to meet the desires and needs of consumers, to provide satisfaction and loyalty to consumers who are the main factors in the success of business. Therefore, consumers expect a quality of performance that can provide satisfaction and customer loyalty by providing quality service, price perceptions and tastes that can make consumers interested. In this study the population is all consumers of " Mie Liho Mie Kiro " Driyorejo District, Gresik. Samples taken were 100 respondents by giving questionnaires to respondents to obtain data. Data analysis techniques used Structural Equation Modeling analysis using Amos 16. The results showed service quality negatively affected customer satisfaction but could positively influence consumer loyalty. Variable price perception can positively influence consumer satisfaction and can negatively affect consumer loyalty. Taste variables can positively influence consumer satisfaction and loyalty. Variable customer satisfaction can positively influence consumer loyalty.